Ghrelin alleviates spinal cord ınjury in rats via ıts anti-inflammatory effects - (:unkn) unknown (My University, 2011)
AMAÇ: Spinal kord hasarı (SKH) primer hasarın yanısıra doku içinde oluşan ikincil hasara yanıt olarak inflamasyona yol açar. Ghrelin 28 amino asit içeren bir peptiddir ve proinflamatuvar sitokinlerin salıverilmesini module ettiği ve antiinflamatuvar etkili olduğu gösterilmiştir. Bu çalışmanın amacı SKH modeli oluşturulan sıçanlarda ghrelinin etkisininin araştırılmasıdır. YÖNTEM ve GEREÇLER: Wistar albino sıçanlar kontrol, SKH ve SKH + ghrelin (10 μg/kg/day, ip) olarak üç gruba bölünmüştür. SKH oluşturmak için T10 düzeyinde orta şiddette yaralanma yapan (100 g/cm kuvvet) ağırlık düşürme yöntemi kullanıldı. Hasar sonrası ilk 15 dakikada ghrelin veya fizyolojik serum uygulandı. Birinci hafta sonunda motor işlev değerlendirilerek dekapitasyon yapıldı. Kanda nöron-spesifik enolaz (NSE) ve S-100β protein düzeyleri ölçüldü. Omurilik dokusunda ise histolojik ve biyokimyasal incelemeler (miyeloperoksidaz aktivitesi (MPO) ve DNA fragmantasyonu) bakıldı. BULGULAR: SKH grubunda kanda NSE, S-100β düzeylerinde ve dokuda MPO aktivitesi, DNA hasarında anlamlı bir artış görüldü. Diğer yandan ghrelin tedavisi SKH’ya bağlı olarak gelişen biyokimyasal ve histolojik değişiklerde düzelme sağlarken, motor işlev skorunda değişiklik yapmadı.

ABSTRACT AIm: Spinal cord injury (SCI) leads to an inflammatory response that generates substantial secondary damage within the tissue besides the primary damage. Ghrelin, 28 amino-acid peptide, has been shown to modulate the release of proinflammatory cytokines and exert antiinflammatory effects. The aim of the current study was to investigate the anti-inflammatory effects of ghrelin, in a rat model of SCI. Ma terIal and Methods: Wistar albino rats were divided as control, SCI, and ghrelin-treated (10 μg/kg/day, ip) SCI groups. In order to induce SCI, a standard weight-drop method that induced a moderately severe injury (100 g/cm force) at T10, was used. Injured animals were given either ghrelin or saline 15 min post-injury. Results: In plasma samples, neuron-specific enolase (NSE) and S-100β protein levels were evaluated. Spinal cord samples were taken for histological examination or determination of myeloperoxidase (MPO) activity and DNA fragmentation. SCI caused significant increases in plasma NSE and S-100β levels and tissue MPO activity and DNA damage. On the other hand, ghrelin treatment improved histological findings as well as biochemical parameters while it failed to improve the impairment of the neurological functions due to SCI. ConclusIon: The present study suggests that ghrelin could reduce SCI-induced oxidative stress and exert anti-inflammatory effects in the spinal cord following trauma.
Ghrelin anti-inflamatuar etkileri yoluyla sıçanlarda spinal kord hasarını azaltır
Keywords: Cerrahi